Nano Zero Valent Iron Composites for Water Decontamination: A Review - Shukla, Nivedita; Saxena, Amit; Gupta, Vatsana; Rawat, Ashok S.; Shrivastava, Sarita; Rai, Pramod Kumar (Current Environmental Engineering, 2018)
Zero valent iron nanoparticles (nZVI or Fe0 nanoparticles) have received enormous attention in recent years due to their promising results against a vast variety of water contaminants. They have proven to be much more effective and fast, in comparison to granular ZVI against these contaminants, due to their small size and large specific surface area. But at the same time, the use of nZVI in water remediation has been limited due to its lower stability under ambient conditions. In order to increase its stability in water and enhance its water decontamination efficiency; the composites of nZVI with clays, polymers, carbon derivatives, metal oxides, biomaterials and polymeric resins are being prepared and studied enormously. This review focuses on the application of nZVI composites for the removal of numerous organic and inorganic toxicants from contaminated water. The plausible mechanism involved in the removal of different types of contaminants has also been discussed.
Keywords: removal mechanisms